Evaluation of the nearest development zone for children with a light degree of intellectual disability who live in an orphanage - Kamińska, Anna Maria; Nadolska, Anna; Blahutková, Marie; Sližik, Miroslav (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The functioning of disabled children living in an orphanage remains little discussed in the scientific literature. Analysing this subject can undoubtedly improve assistance and revalidation*, as well as helping them become independent. This was the main reason for our interest in this research topic. Aim of Study. The aim of this study was to try to answer the following question: do children with intellectual disabilities who live in an orphanage encounter an environment that is favourable for their development or unfavourable compared to children living in their family home? Material and Methods. Three groups of children aged 12-13 years with light intellectual disability were examined (n = 90). The three groups, each consisting of 30 children, included those who had lived in an orphanage for a short period of time, those who had lived in an orphanage for a long period of time, and those who lived in their family home. This research used a method developed at the school of L. Vygotsky to measure the area of nearest development, a clinical measure based on the determination of skillfulness. Results. The most important finding was that there are no differences in the area of nearest development between children living in orphanages and those living in their family home. The best developed zone was found to be motor development, with children living in orphanages scoring the highest in that area. Conclusions. Contrary to assumptions, the home environment did not adversely affect the development of the examined children. There was a similar current level of development in all three zones among children with a light degree of intellectual disability living in orphanages and in family homes. Therefore, the orphanage environment can be considered a positive developmental environment for these children.
Keywords: orphanage; light degree of intellectual disability; zone of nearest development; untapped development potential; exploited development potential; cognitive development; social development; motor development